FR2.1: An Exploration of Gender norms and Women's Empowerment: The Case of Dairy Related Businesses in Kilimanjaro and Tanga, Tanzania - Achandi, Esther L.; Galiè, Alessandra; Omore, Amos O.; Jeremiah, Adolf (International Livestock Research Institute, 2022)
Although women play a major role in the dairy sub-sector in Tanzania, they still face several barriers in accessing and benefitting from marketing of livestock and livestock related products. Gender norms particularly affect their participation and access to benefits from livestock value chains. This study uses a qualitative methodology to explore gender norms that affect women's engagement in dairy-related businesses and the local context conceptualization of empowerment. Initial findings indicate that; In the past, a woman's role was to take care of her husband, children and cows therefore women often work from home. Men do not sell milk in the market and do not cut fodder for sale except fodder for their own cattle (in Moshi, Kilimanjaro) thus such activities were therefore mainly done by women. Traditionally, a man was responsible for external matters and men were thus more mobile and better networked than the women. A woman is a pambo la nyumba (household decoration) and cannot take care of the children and cows at the same time (in Muhweza, Tanga); therefore, few women engaged in dairy related businesses. A woman should not take a cow to mate with a bull nor engage in cattle artificial Insemination (AI) and because of this norm, businesses providing such services were predominantly owned by men. Women's engagement in livestock related businesses is greatly hinged around existing norms and so is their empowerment. Interventions seeking to engage with women's empowerment ought to take gender norms into consideration.